Performance Improvement Strategy for Independent Assurance Services at PT Indonesian Classification Bureau (Persero) Belawan Commercial Branch - Abd. Rahman; Retno Kusumastuti (International Journal of Economics Development Research (IJEDR), 2023)
Independent assurance services have the characteristics of a complex environment and high uncertainty. The product life cycle is very short which is easily imitated by other companies and immediately replaced by new products with more sophisticated technology. This requires companies to continuously carry out business development to grow sustainable competitive advantages and overcome a very dynamic and complex competitive environment. This research is quantitative descriptive research with a qualitative approach, namely research that describes the condition of the object under study in the form of direct observation, conducting Focus Group Discussions and surveys using questionnaires. The data analysis method used in this study is an analysis using the SWOT matrix to determine alternative strategies. From the results of the SWOT analysis, five priority strategies were obtained to improve the performance of PT BKI Belawan Branch in carrying out independent assurance services. First, maintaining and improving quality to compete with foreign companies or other competing companies in synergy with other holding companies. These can be done through competitor analysis by evaluating the strengths and weaknesses of competitor companies. Second, making cooperation MoUs consistently with external partners in several cities. Third, continuing business improvement ethics and accountability to shareholders. Fourth, exchanging the test equipment with a different tool or the test is carried out in another laboratory that meets the requirements. Fifth, if the technician uses improper procedures, the technician will need to be retrained by certified project personnel.